Exploring Anaphoric and Cataphoric References Used in â€œBright, an English Textbookâ€ - Muhammad Sabaniyah; Didin Nuruddin Hidayat; Nida Husna; Alek Alek (Institut Agama Islam Negeri Palopo, 2023)
This study aims to investigate the use of anaphoric and cataphoric references in narrative text in â€œBright An Englishâ€ Textbook for 8th-grade junior high school students, and to identify the most commonly used in the texts. This study examined the data that contained the anaphoric and cataphoric by the theory of Halliday and Hasan (1976). The study used a qualitative descriptive approach because it dealt with descriptive. The main data for this study was â€œBright, an English textbookâ€ for 8th-grade junior high school students, written by Nur Zaida and published by Erlangga. The results showed those anaphoric and cataphoric references contained in the English textbook; 22 sentences had anaphoric and cataphoric references in detail of which fifteen sentences were anaphoric, and seven sentences were cataphoric. â€œBright, an English textbookâ€ for eighth-grade junior high school students frequently uses pronominal anaphora because it addresses the referent of the anaphora with a pronoun. Pronouns were important because they linked sentences, which helped to avoid the nouns being used repeatedly. Besides, the cataphoric reference was rarely used, which is considered more difficult for 8th graders to understand.